Omalizumab for the treatment of severe persistent allergic asthma: a systematic review and economic evaluation - G Norman; R Faria; F Paton; A Llewellyn; D Fox; S Palmer; I Clifton; J Paton; N Woolacott; C McKenna (Health Technology Assessment, 2013)
Background: Allergic asthma is a long-term disorder of the airways resulting from overexpression of immunoglobulin E (IgE) in response to environmental allergens. Patients with poorly controlled asthma are at high risk of exacerbations requiring additional treatment, including hospitalisations. Severe exacerbations are potentially life threatening. Guidelines identify five treatment steps for both adults and children. Omalizumab (Xolair®) is a recombinant DNA-derived humanised monoclonal antibody indicated as an add-on therapy in patients aged ≥ 6 years with severe persistent allergic asthma uncontrolled at treatment step 4 or 5. Objective: To determine the clinical effectiveness, safety and cost-effectiveness of omalizumab, as an add-on therapy to standard care, within its licensed indication, compared with standard therapy alone for the treatment of severe persistent allergic asthma in adults and adolescents aged ≥ 12 years and children aged 6–11 years. Data sources: Eleven electronic databases (including MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials) and additional sources including regulatory agency reports were searched from inception to October 2011. Additional data sources include: the manufacturer’s submission (MS); two previous National Institute for Health and Care Excellence (NICE) single technology appraisal (STA) submissions; and existing reviews on the safety of omalizumab and oral corticosteroids (OCSs). Review methods: Systematic reviews of the clinical effectiveness and cost-effectiveness evidence for omalizumab were performed. The primary outcome was number of clinically significant (CS) exacerbations. Other outcomes included asthma symptoms, unscheduled health-care use, asthma-related mortality, OCS use and health-related quality of life (HRQoL). Because of methodological and clinical heterogeneity between trials, a narrative synthesis was applied. Pragmatic reviews with best evidence syntheses were used to assess adverse events of omalizumab and OCSs. The cost-effectiveness of omalizumab was assessed from the perspective of the UK NHS in the two separate populations: adults and adolescents, and children, using a cohort Markov model. Costs and outcomes were discounted at 3.5% per annum. Results are presented for additional subgroup populations: (1) hospitalised for asthma in the previous year, (2) adults and adolescents on maintenance OCSs and (3) three or more exacerbations in the previous year. Results: Eleven randomised controlled trials (RCTs) and 13 observational studies were identified, including four RCTs/subgroups in the adult licensed population and one subgroup in children. A minority of patients were on maintenance OCSs. No evidence comparing omalizumab with OCSs was identified. Omalizumab significantly reduced the incidence of CS exacerbations in both adults and children [adults: INvestigatioN of Omalizumab in seVere Asthma Trial (INNOVATE): rate ratio 0.74; 95% CI 0.55 to 1.00; children IA-05 EUP (the a priori subgroup of patients who met the European Medicines Agency license criteria) 0.66; 95% CI 0.44 to 1.00]. Significant benefits were observed for a range of other outcomes in adults. Subgroup evidence showed benefits in adults on maintenance OCSs. Evidence for an OCS-sparing effect of omalizumab was limited but consistent. Omalizumab is available as 75 mg and 150 mg prefilled syringes at prices of £128.07 and £256.15 respectively. The incremental cost-effectiveness ratio (ICER) for adults and adolescents is £83,822 per quality-adjusted life-year (QALY) gained, whereas the ICER for children is £78,009 per QALY gained. The results are similar for the subgroup population of ≥ 3 exacerbations in the previous year, whereas the ICER for the other subgroup populations are lower; £46,431 for the hospitalisation subgroup in adults and adolescents, £44,142 for the hospitalisation subgroup in children and £50,181 for the maintenance OCS subgroup. Conclusion: Omalizumab reduces the incidence of CS exacerbations in adults and children, with benefits on other outcomes in adults. Limited, underpowered subgroup evidence exists that omalizumab reduces exacerbations and OCS requirements in adults on OCSs. Evidence in children is weaker and more uncertain. The ICERs are above conventional NHS thresholds of cost-effectiveness. The key drivers of cost-effectiveness are asthma-related mortality risk and, to a lesser extent, HRQoL improvement and OCS-related adverse effects. An adequately powered double-blind RCT in both adults and children on maintenance OCSs and an individual patient data meta-analysis of existing trials should be considered. A registry of all patients on omalizumab should be established. Study registration: The study was registered as PROSPERO CRD42011001625. Funding: This report was commissioned by the National Institute for Health Research Health Technology Assessment programme on behalf of NICE as project number HTA 10/128/01.